An infinite servers model for motor vehicles dismantling and recycling in a scarce energy ambience - Ferreira, M. A. M.; Filipe, J. A. C. B.; Coelho, M. F. P.; Andrade, M. (Proceedings of the International Conference Quantitative Methods in Economics (Multiple Criteria Decision Making XIV), 2008)
We propose the M|G|∞ queue system to analyze a situation at which conventional motor vehicles will be out of use as far as the usual energy sources will be exhausted. Two possibilities are posed: recycling or dismantling. Using the hazard rate function we conclude that when the rate of dismantling and recycling of motor vehicles is greater than the rate at which they become idle, the situation tends to get balanced. The motor vehicles that are unused with the conventional energies either turn useful with another kind of energies or are included in other useful devices.